1976
DOI: 10.1128/aac.10.1.119
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral Action and Cellular Toxicity of Four Thymidine Analogues: 5-Ethyl-, 5-Vinyl-, 5-Propyl-, and 5-Allyl-2′-Deoxyuridine

Abstract: 5-Ethyl-, 5-vinyl-, 5-propyl-, and 5-allyl-2'-deoxyuridine (dUrd) had antiviral activity against herpes simplex type 1 and type 2 grown in HeLa TK-cells, in the order 5-vinyl-dUrd, 5-ethyl-dUrd, 5-propyl-dUrd, 5-allyl-dUrd, but they were inactive against a TK-mutant of herpes simplex type 1. The antiviral activity of these compounds could be partially reversed by thymidine. Except for 5-vinyl-dUrd, they were not toxic to WI-38 and HeLa TK-cells at a concentration of 25 ,uM. All four analogues inhibited the gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
31
0

Year Published

1978
1978
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 106 publications
(32 citation statements)
references
References 9 publications
1
31
0
Order By: Relevance
“…These results suggest that L-I-OddU could serve as a "selective alternate substrate" as described in our previous study (5) and can explain the good selective therapeutic index observed with this compound. While EBV TK appears to be responsible for the formation of L-I-OddUMP, further phosphorylation may occur by human dTMP kinase and NDP kinase to form L-I-OddUDP and L-I-OddUTP, respectively.…”
Section: Discussionsupporting
confidence: 82%
“…These results suggest that L-I-OddU could serve as a "selective alternate substrate" as described in our previous study (5) and can explain the good selective therapeutic index observed with this compound. While EBV TK appears to be responsible for the formation of L-I-OddUMP, further phosphorylation may occur by human dTMP kinase and NDP kinase to form L-I-OddUDP and L-I-OddUTP, respectively.…”
Section: Discussionsupporting
confidence: 82%
“…A new approach has evolved from the discovery in 1963 of a virally specified enzyme, thymidine kinase (TK) in HSV-infected cells (7). The specificity of this enzyme allows it to selectively trap certain nucleoside analogs within HSV-infected cells and has been of use in developing effective antiviral drugs with low toxicity (3,6). It also offers the promise that a nucleoside analog labeled with a gamma-emitting isotope might be of value in detecting HSV infections and could be utilized in a selective brain scan for HSV encephalitis.…”
mentioning
confidence: 99%
“…Virus-specific DNA polymerase (deoxynucleoside triphosphate:DNA nucleotidyltransferase, EC 2.7.7.7) is one of the target enzymes most suitable for this purpose (1)(2)(3). Several nucleoside analogs inhibit virus replication by affecting this enzyme (4)(5)(6)(7)(8)(9). Acyclovir [ACV; 9-(2-hydroxyethoxymethyl)guanine] is one of a class of antiviral compounds recently shown to be effective in a variety of herpesvirus infections in vitro and in animal models (10).…”
mentioning
confidence: 99%